Penerapan Diseminasi Bioteknologi Pemanfaatan Eceng Gondok, Eichornia Crassipes, sebagai Pakan Buatan Alternatif Untuk Pembudidaya Ikan di Sumatera Barat - Efrizal Efrizal; Rusnam Rusnam (Jurnal Pengabdian Warta Andalas, 2016)
This community service activities conducted for the purpose of dissemination of biotechnology utilization of water hyacinth, Eichornia crassipes, as one of the raw materials alternative artificial feed and increasing their knowledge and skills of fish farmers (public) Koto Tangah Village in the business of making the pellets fish in West Sumatra, so hopefully they can do maintenance in a manner / good technique and environmentally friendly. In addition, these service activities are also expected to be able to reduce operating costs in the maintenance of fish and could ultimately increase the income of farmers village of Koto Tangah through the development of sustainable fish farming. To achieve optimal results, the community service that the main target of community service in the District of Koto Tangah this is a fish farmer groups and the coaches / leaders Bangek River villagers are expected to be able to motivate the farmers to promote alternative methods of making artificial feed for the development of freshwater fish farming environmentally friendly. The method used in this activity are (1) Lecture, the main material: (a) provide knowledge about a wide range of raw materials that can be used to feed the fish, (b) provide knowledge about the preparation of formula / artificial food composition, (c) provide knowledge about the process of making artificial food (d) increase the public's knowledge about how to save a good pellet to be more durable and (e) the provision of quality testing of feed materials, whether physical, chemical and biological; and (2) Demonstration of making fermented hyacinth and manufacture of pellets / fish feed alternative to the fermentation mixture of water hyacinth. The results of this IbM service activities found that the knowledge and skills of Sawah Laweh farmer groups and Batang Kandis Jaya farmer groups fishing in Sungai Bangek Village Kelurahan Balai Gadang, Koto Tangah District, Padang, before being implemented IbM service activities is still very low. However, the motivation or desire IbM partner community farmer groups to undertake the cultivation or maintenance of very large fish. It is apparent from the community farmer groups IbM partners to master the manufacturing technology of fermented fish feed water hyacinth relatively high. Furthermore, the results of these community service activities to increase knowledge and skills of the community in the search for alternative feed for aquaculture fish feed that can work well in both areas IbM partners. In order for farming activities run well in both areas IbM partners necessary to service activities on an ongoing basis about the alternative technique of making fish pellets and fish maintenance techniques that efficiently and effectively. Besides, it is necessary to support the provision of funds or credit by the authorities to the public or the fish farmers to capital development efforts.